How Supply Chain Management Practices Influence Customer Development and Operational Performance - Muhammad, Hafidz Ummay; Isfianadewi , Dessy (Publikasi Indonesia, 2023)
This study was undertaken to measure the supply chain management practices affected customer development and operational performance at small and medium-sized businesses (SME) that distributed liquefied petroleum gas (LPG). The dataset contains 103 SMEs in East Kotawaringin, Indonesia. Quantitative techniques were employed in this research, and Employing questionnaire to collect data. To analyze the data for this investigation, partial least square structural equation modeling (PLS-SEM) was used. The outcomes of all variables' data analysis have a significant effect on all other variables in this model. The study's findings show that supply chain management practices have a significant impact on customer development and operational performance, while customer development has a positive and significant impact on operational performance. Furthermore, Customer development can act as a mediator in the interaction between operational performance and supply chain management. The study's conclusions have some relevance for LPG retailers.